(untitled) (Scientific journal of the Fergana State University, 2026)
This article scientifically substantiates the prospective opportunities for tourism development in the Sangzor River basin, considering its natural-geographical conditions, landscape structure, and the presence of natural sites. The recreational potential of the region, its ecological status, existing problems, and future development directions are analyzed. The study was conducted based on GIS data, cartographic materials, and field observations.